Increased levels of serum Wisteria floribunda agglutinin-positive Mac-2 binding protein in idiopathic pulmonary fibrosis. (June 2016) - Kono, Masato; Nakamura, Yutaro; Oyama, Yoshiyuki; Mori, Kazutaka; Hozumi, Hironao; Karayama, Masato; Hashimoto, Dai; Enomoto, Noriyuki; Fujisawa, Tomoyuki; Inui, Naoki; Yamada, Masaomi; Hamada, Etsuko; et al.
Abstract: Background: Mac-2 binding protein (M2BP) is a cell-adhesive glycoprotein of the extracellular matrix secreted as a ligand of galectin-3 (Mac-2). Recently, a Wisteria floribunda agglutinin positive-M2BP ( WFA + -M2BP) assay developed using a lectin-antibody sandwich immunoassay has shown promise as a new fibrotic marker in liver fibrosis to detect unique fibrosis-related glycoalteration. The aim of this study is to evaluate the utility of serum WFA + -M2BP levels in patients with idiopathic pulmonary fibrosis (IPF). Methods: We measured serum WFA + -M2BP levels in 116 patients with IPF and 42 healthy volunteers. We examined the relationship between serum WFA + -M2BP levels and clinical parameters and further investigated the prognostic significance of serum WFA + -M2BP levels in patients with IPF. Results: Serum WFA + -M2BP levels were significantly higher in patients with IPF than in healthy controls (1.09 ± 0.89 cutoff index [COI], 0.57 ± 0.24 COI, respectively; P < 0.001). In patients with IPF, a significant positive correlation was found between serum WFA + -M2BP levels and age, KL-6, neutrophils in BAL, reticulation and honeycombing scores in HRCT, and fibrotic foci scores in pathological findings, and a significant negative correlation was found between serum WFA + -M2BP levels and FVC, %DLco and macrophages in BAL. Furthermore, patients with high serum WFA + -M2BP levels had a significantly worse prognosis than those with low levels (log-rank test, P = 0.0209), and a high serum WFA + -M2BP level was a significant prognostic factor in Cox proportional hazards regression analysis. Conclusions: Our results suggest that the serum WFA + -M2BP level is a potential biomarker in patients with IPF. Highlights: Serum WFA + -M2BP levels were significantly higher in IPF than in healthy controls. M2BP expressed in proliferating type II alveolar cells and fibroblastic foci in IPF. Serum WFA + -M2BP levels were associated with the progression of pulmonary fibrosis. High serum WFA + -M2BP levels were related to poor prognosis in IPF.